(untitled) (Research, Society and Development, 2023)
In the last year, all nations have been experiencing the advance of the viral pandemic caused by the new coronavirus. In this way, the researchers began an intense search for clear and correct information, in order to find a way to contain its advance. The present research project aims to synthesize the main points about SARS-CoV-2, its immunopathological mechanisms and host aggression, through data collection based on recent publications. Through the literature review, it was concluded that, after host infection, tissue damage in several organs can lead to acute injuries and sequelae after pathogen elimination. Finally, the relationship between the vaccine and the reduction of complications from the disease was seen.